«The Russian paradox»: high education/low human capital - Николас Эберштадт (Демографическое обозрение)
Some aspects of contemporary Russia’s population profile — such as its depopulation and steady surfeit of deaths over births — once seemed distinctive, but are today increasingly common in both Europe and the UN’s other «developed regions». But other aspects still remain highly distinctive. We examine one of those here: we call it Russia’s «high education/low human capital paradox». Despite levels of schooling comparable to other European countries, and to developed countries in other regions, Russian adult mortality levels are no better than «Third World», and by some measures, actually look «Fourth World», e.g. in countries with the lowest level of socio-economic development. Furthermore, despite its sizeable cadre of highly educated men and women, Russia also appears to have serious problems with «knowledge creation». Projections suggest Russia’s working-age adult mortality profile will remain unfavorable for decades to come, and that Russia’s global share of highly educated manpower is set to decline over the coming generation. There are economic and potentially geopolitical implications to such trends. We conclude by noting similarities to Russia’s high education/high adult mortality elsewhere in the former Soviet space.